Pulsed electromagnetic fields and ozone in the treatment of the knee Arthrosis in elderly patients (Ozone Therapy Global Journal, 2016)
Objective: Evaluate the effect of pulsed electromagnetic fields as treatment for arthrosis of the knee and combination of these with intra-joint infiltration of ozone in elderly patients.  Method: A longitudinal and prospective study was performed in 90 patients older than 60 years of age, with clinical and radiological diagnosis of grade II and III knee arthrosis resistant to medical treatment, who attended ozone therapy consultation at the Policlinic Ramp between January and December of 2014. The population was divided in three groups: 1) AINES, Control, Non Steroid Anti-Inflammatory was administered. 2) 10 sessions of pulsed electromagnetic fields (PEMF) with a frequency of three per week were administered. 3) 10 sessions of pulsed electromagnetic fields (PEMF) with a frequency of three times per week were administered and 10 intraarticular infiltrations with ozone with a frequency of three times per week. All the results were evaluated before and after the treatment the pain perceived by means of the visual analogical scale of the pain (EVA), the intervening functionality was evaluated the administration of the questionnaire WOMAC (The Western Ontario and McMaster Universities Osteoarthritis Index): the degree of clinical improvement, the minimal amount of therapy applications to achieve improvement and the incidence of side effects. Results: The protocol used with PEMF therapy for arthrosis of the knee was very superior to the application of AINES with a statistically important difference (p=0, 00) and the results were even better when they were combined with intra-joint infiltrations of ozone. In the groups treated with ozone and pulsed electromagnetic fields there were no side effects reported as for in the groups treated with AINES there were gastrointestinal and elevated high blood pressure side effects manifested.  Conclusion: Treatments with pulsed electromagnetic fields for arthrosis of the knee grade II and III are safe and effective methods, and potentiate when combined with ozone intra-joint infiltrations